PARADOKS DESENTRALISASI PERUMAHAN DI INDONESIA STUDI KASUS KOTA PALEMBANG DAN KOTA PEKALONGAN - Mahditia Paramita (Universitas Gadjah Mada, 2014)
Housing decentralization not only positions housing sector as regional obligatory, but also triggerspublic expectations upon the improvement of housing conditions. Various weaknesses of centralizedsystem that full of generalization in housing policy makes decentralized system is interpreted as aninnovative renewal process. However, the central government still does a lot of intervention towardhousing program. Limitation happens to local government such as limitation in housing finance,weakness in coordination ability, and less established of local bureaucracy makes intervention fromcentral government in housing program financed by APBN always dominates. The least contributionfrom local government on public housing sector in decentralization era creates paradox. It is caused bythe Ministry of Public Housing (Kemenpera) that cannot perform fully as substitutional institution rolein managing housing in local area. Kemenpera position as ministerial cluster 3 makes them does nothave representative office in local area. Thus, there will be potential of a repeat experience in the past, inform of generalization in housing policy, that complicates the housing problems itself.